Challenges Of Asset Management In The Healthcare Industry: A Case Study Of Central Hospital Zhuzhou, China - Yu, Weiya (2023)
Asset management refers to the systematic and strategic approach to planning, procurement, utilization, maintenance, and disposal of assets to maximize their value and minimize their associated risks and costs over their entire lifecycle. In the healthcare industry, asset management involves the efficient and effective management of physical and intangible resources such as medical equipment, facilities, IT systems, and human capital. Asset management aims to ensure that these resources are optimized for patient care, financial sustainability, and operational efficiency. This research paper aims to investigate the challenges associated with asset management in the healthcare industry, including asset inflow, outflow, procurement, disposal, and the influence of the information technology (IT) workforce on asset management and the healthcare industry. Research on asset management in the healthcare industry is relatively scarce. Against the backdrop of the global pandemic, issues related to the entire lifecycle of medical assets and technology management have become prominent. Based on the insights from the literature review, theoretical frameworks from previous studies related to the research question were synthesized. This research used qualitative methods to explore the understanding of the topic and employed an interview method for data collection and analysis. This research interviewed seven healthcare industry respondents with more than five years of experience in asset management. The primary findings suggest that effective asset management and a robust IT technical team are crucial for streamlined healthcare industry operations and can significantly enhance operational efficiency. The research paper also highlights the importance of timely procurement and accurate disposal of assets in addressing operational challenges. In conclusion, the research paper found that asset management in the healthcare industry is a complex and multifaceted issue that requires a comprehensive and integrated approach. The integration of information technology, the development of a robust asset management system, and the cultivation of specialized talent are crucial elements in addressing the challenges faced by the healthcare industry. The research paper's findings and conclusions can guide other healthcare institutions facing similar issues and challenges in asset management. By contributing to the existing literature in the healthcare industry, this research paper validates and extends the understanding of the essential role asset management plays in sustaining and improving healthcare services in the future by including more profound reflections and long-term discussions regarding the introduction of IT technology and the training and development of personnel in the healthcare industry.